Effect of adipose graft transposition procedure (AGTP) on the ischemic arrhythmogenic substrate: an MRI study in a swine model of chronic myocardial infraction. (24th May 2021) - Adelino Recasens, R; Galvez-Monton, C; Teis, A; Martinez-Falguera, D; Rodriguez-Leor, O; Fadeuilhe, E; Sarrias, A; Villuendas, R; Bazan, V; Aranyo, J; Prat, C; Bayes-Genis, A; et al.
Abstract: Funding Acknowledgements: Type of funding sources: Public grant(s) – National budget only. Main funding source(s): Instituto de Salud Carlos III BACKGROUND: Cardiac regenerative therapy is a promising treatment for patients with myocardial infarction (MI) and heart failure. Nevertheless, previous ex-vivo studies have raised concern on the potential increased risk of arrhythmic events following certain cell therapies. Adipose graft transposition procedure (AGTP) is a cardiac reparative therapy consisting in transposing a vascularized adipose flap from the autologous pericardium and placing it over the epicardial scar area and has demonstrated to reduce infarct size and improve the left ventricular ejection fraction in preclinical and human studies. PURPOSE: To assess the effect of the AGTP on the post-MI scar composition and image-based ventricular tachycardia (VT) corridors detection by means of late gadolinium enhanced cardiac magnetic resonance (LGE-CMR). METHODS: A left circumflex artery (first marginal branch) MI was induced in 9 Landrace X Large White Pigs by delivering 1-3 coils. Two weeks post-MI, all subjects underwent a 3 Tesla LGE-CMR and randomized to the AGTP or sham group. LGE-CMR was repeated 30 days post-treatment (6 weeks post-MI). The arrhythmogenic substrate was characterized with an advanced image post-processing tool (ADAS 3D) and included quantification of dense scar and border zone (BZ) mass and detection of ventricular tachycardia (VT) corridors (including corridor scar mass). RESULTS: The overall scar mass did not differ between scans in the overall population (7.6 ± 3.5 g vs 7.5 ± 2.2 g in the baseline and post-treatment scans, respectively; p = 0.9). Compared to the sham subjects, those receiving AGTP showed an absolute reduction of the total (-3.2 ± 1.4 g vs. +2.4 ± 1.7 g, p = 0.04) and dense scar (-0.9 ± 0.4 g vs. +0.7 ± 0.5 g, p = 0.03). BZ mass tended to decrease in the AGTP group (-2.2 vs 1.63 g; p = 0.06). The AGTP group showed a trend to reduce the number of VT corridors (-1 ± 0.7 vs. +0.4 ± 0.2, p = 0.078) and corridor scar mass (-0.3 ± 0.26 g vs. +0.1 ± 0.1 g, p = 0.11) (figure). CONCLUSIONS: Cardiac reparative therapy of MI with AGTP reduced dense scar mass, compared to the increase observed in the sham group. The trend to reduce the BZ mass and the number/mass of VT corridors suggests a beneficial effect on the arrhythmic remodeling of the post-MI scar.